Transient response of ARROW VCSELs - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2005)
The transient response of antiresonant reflecting optical waveguide (ARROW) vertical-cavity surface-emitting lasers (VCSELs) is analyzed. It is found that under current modulation, the radiation loss of the transverse-leaky mode decreases during the state of the lasers but increases during the state. Numerical analysis shows that this variation in radiation loss is due to the carrier-induced refractive-index depression that arises from spatial-hole-burning of carrier concentration. It is noted that the increment in radiation loss during the state can be used to prevent net modal gain of the transverse-leaky mode from reacquiring threshold after turn-off. Hence, a new method to design ARROW, based on the variation in radiation loss, is proposed to eliminate the excitation of secondary pulsation in VCSELs. The influence of thermal lensing effects on the excitation of secondary pulsation during the state of the lasers is also investigated.